KILAS BALIK PROGRAM PENDIDIKAN GURU PENGGERAK (PGP) - Riswakhyuningsih, Tri; Setyaningrum, Dewi (Bapelitbang Kabupaten Batang, 2025)
ABSTRACT The purpose of the study is to provide an overview of the material studied and the learning flow in the Teacher Leader Education. The study was conducted using a qualitative method. The data sources were the material and learning flow of the Teacher Leader Education. Data were collected by reviewing modules, exploring the Learning Management System, and the researcher's personal experience as a Teacher Leader Education participant. Data analysis was carried out using triangulation techniques. There were 10 modules studied: 1) the national education philosophy of Ki Hadjar Dewantara; 2) the values ​​and roles of the teacher leader; 3) the vision of the teacher leader; 4) positive culture; 5) learning to meet student learning; 6) social and emotional learning; 7) coaching for academic supervision; 8) decision making based on virtue values ​​as a leader; 9) leaders in resource management; and 10) program management that has a positive impact on students. Learning flow: starting from self, concept exploration, collaboration space, contextual demonstration, elaboration of understanding, connections between materials, and real action. Keywords: Ki Hadjar Dewantara, Independent Learning, Teacher Education for Leaders